Solved after 140 years: the identity of the millipede Polydesmus cavicola Packard, 1877, and proposal of Packardesmus n. gen. (Diplopoda: Polydesmida: Macrosternodesmidae) - Shear, William A.; Shelley, Rowland M. (Zootaxa, 2019)
The identity of Polyesmus cavicola Packard, 1877, described from a cave in Utah, is clarified through examination of a female lectotype and a newly collected adult male. The species is placed in the family Macrosternodesmidae and is designated as the type species of Packardesmus, n. gen.